Golden cross as buying indicator for stock investment in Bursa Malaysia / Eng Wat Kim ... [et al.] - Kim, Eng Wat; Abd Shukor, Nadeeya Eli Syaheerah; Ismail, Nur Rashidah; Abdul Halim, Syazwani (2012)
There are many factors affecting the performance in stock markets, causing difficulties for traders in ascertaining the right time for them to purchase shares. This paper analyzes the use of the Golden Cross as an indicator for buying stock, based on the stock market of Bursa Malaysia from June 2008 until January 2011. The 30 most active counters from Bursa Malaysia were analyzed. This project compared the returns of buying at golden crosses of various EMA and selling at (i) Death Cross, (ii) highest price before Death Cross and (iii) at the peak of short EMA, using three pairs of EMA, namely EMA 50 and 100, EMA 50 and 200, and EMA 100 and 200. Results show that buying at Golden Cross with high volume and selling at peak of short EMA before the formation of Death Cross is a reliable method for investors because it gives a consistent return.